Role of Brain-Derived Neurotrophic Factor in Beneficial Effects of Repetitive Transcranial Magnetic Stimulation for Upper Limb Hemiparesis after Stroke - Niimi, Masachika; Hashimoto, Kenji; Kakuda, Wataru; Miyano, Satoshi; Momosaki, Ryo; Ishima, Tamaki; Abo, Masahiro (PloS one, 2016)
Repetitive transcranial magnetic stimulation (rTMS) can improve upper limb hemiparesis after stroke but the mechanism underlying its efficacy remains elusive. rTMS seems to alter brain-derived neurotrophic factor (BDNF) and such effect is influenced by BDNF gene polymorphism. To investigate the molecular effects of rTMS on serum levels of BDNF, its precursor proBDNF and matrix metalloproteinase-9 (MMP-9) in poststroke patients with upper limb hemiparesis. Poststroke patients with upper limb hemiparesis were studied. Sixty-two patients underwent rehabilitation plus rTMS combination therapy and 33 patients underwent rehabilitation monotherapy without rTMS for 14 days at our hospital. One Hz rTMS was applied over the motor representation of the first dorsal interosseous muscle on the non-lesional hemisphere. Fugl-Meyer Assessment and Wolf Motor Function (WMFT) were used to evaluate motor function on the affected upper limb before and after intervention. Blood samples were collected for analysis of BDNF polymorphism and measurement of BDNF, proBDNF and MMP-9 levels. Two-week combination therapy increased BDNF and MMP-9 serum levels, but not serum proBDNF. Serum BDNF and MMP-9 levels did not correlate with motor function improvement, though baseline serum proBDNF levels correlated negatively and significantly with improvement in WMFT (ρ = -0.422, p = 0.002). The outcome of rTMS therapy was not altered by BDNF gene polymorphism. The combination therapy of rehabilitation plus low-frequency rTMS seems to improve motor function in the affected limb, by activating BDNF processing. BDNF and its precursor proBDNF could be potentially suitable biomarkers for poststroke motor recovery.